Classification and trends in knowledge research relevance and context for smart farm technology development - Paweena Suebsombut (2018)
© 2017 IEEE. With the climate change paradigm, farmers are facing changes in the environment all the time like drought, higher temperature, heavy raining, and the shift of season. Smart farm is a method for helping farmers to plant their crops efficiently. This paper reviews the relevance and context for smart farm development in terms of technology, knowledge for farming, and Life Cycle Management (LCM). The literature shows that several research studies have adopted smart farm technology to monitor and control farm which can help farmers improving their production process and practices. Consequently, the exploit between knowledge for farming and data collected on farm by using smart farm technology is interesting for decision making that can help farmers to manage agricultural production and control the production process more effectively. This research could contribute to identifying the trends and future direction of smart farm technology development.